Underwater versus conventional endoscopic mucosal resection for colorectal lesions: An updated meta-analysis of randomized controlled trials - Chowdhury, Aneesa Rahman; Kim, Jin Sun; Xu, Mimi; Tom, Chloe; Narala, Rachan; Kong, Niwen; Lee, Helen; Vazquez, Alejandro; Sahakian, Ara; Phan, Jennifer; Buxbaum, James (Endoscopy International Open, 2023)
Background and study aims Colorectal malignancy is a leading cause of death. Conventional endoscopic mucosal resection (CEMR) is a strategy used to resect precancerous lesions that involves injecting fluid beneath a polyp to create a gap for resection. Underwater endoscopic mucosal resection (UEMR) is a newer method that forgoes injection, instead filling the intestinal cavity with water to facilitate polyp resection. Our aim was to compare the safety and efficacy of these approaches by synthesizing the most contemporary evidence.Methods PubMed, Embase, and Cochrane libraries were searched from inception through November 11, 2022 for randomized controlled trials (RCTs) comparing UEMR and CEMR for resection of colorectal lesions. The primary outcome was the rate of en bloc resection and secondary outcomes included recurrence, procedure time, and adverse events (AEs).Results A total of 2539 studies were identified through our systematic literature search. After screening, seven RCTs with a total of 1581 polyps were included. UEMR was associated with significantly increased rates of en bloc resection (RR 1.18 [1.03, 1.35]; I2 = 76.6%) versus conventional approaches. No significant differences were found in procedure time, recurrence, or AEs.Conclusions UEMR is a promising effective technique for removal of colorectal lesions. The most contemporary literature indicates that it improves en bloc resection rate without increasing procedure time, recurrence, or AEs (PROSPERO ID CRD42022374935).
Keywords: Polyps / adenomas / ...; Endoscopy Lower GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...); Colorectal cancer